ASSAY OF ENGLISH CUISINE: ADVENT AND ADVANCEMENT - Raj, A. Steve Roger; Eugene, J. (International Journal of Research -GRANTHAALAYAH, 2020)
England is a country that has experienced various changes throughout the course of its history. From its land being invaded to colonizing in other lands, the cuisine has been under the constant state of adaptation and improvisation in order to meet the dietary needs of the people. This research is done to give an insight into the English Cuisine with respect to history in order to better elucidate the nature of the English food in adaptive flux through the centuries. This study shows historical data excavated from evidential books published throughout those centuries as well as articles and data published on the subject. The objectives of the research done are: To understand the nature of the English cuisine. To understand the history and origin of the English food developed. To understand the influences the cuisine had on other countries. To analyze the past events and the changes made that affect the current English Cuisine and evolution undergone. To better understand the future of the cuisine in terms of survival.